(untitled) (Integral : Pendidikan Matematika, 2019)
This study aims to determine the differences in increasing the ability of mathematical representation and the acquisition of mathematical problem solving abilities between students who get learning with a scientific approach based on contextual problems with students who get expository learning. This type of research is quasi-experimental. The sample was 79 VII grade students who came from two classes in one State Junior High School in Lembang Regency. First class gets learning with a scientific approach based on contextual problems and the second class gets Expository learning. Both classes posttest mathematical problem solving abilities. The results showed that (1) there was a difference in the overall acquisition of mathematical problem solving abilities between students who studied with a scientific approach based on contextual problems and students who received expository learning; (2) there are differences in the acquisition of mathematical problem solving abilities based on students’ initial mathematical abilities (high, medium, low) (3) there is an influence of interaction between the learning model and students’ initial mathematical abilities on improving students’ mathematical problem solving abilities. Keywords: Learning Scientific Approach Based on Contextual Problems, Mathematical Problem Solving